Longitudinal assessment of short‐term memory deterioration in a logopenic variant primary progressive aphasia with post‐mortem confirmed Alzheimer's Disease pathology. Issue 2 (18th April 2014) - Tree, Jeremy; Kay, Janice
<x xml:space="preserve">Abstract</x> In the field of dementia research, there are reports of neurodegenerative cases with a focal loss of language, termed primary progressive aphasia (PPA). Currently, this condition has been further sub‐classified, with the most recent sub‐type dubbed logopenic variant (PPA‐LV). As yet, there remains somewhat limited evaluation of the characteristics of this condition, with no studies providing longitudinal assessment accompanied by post‐mortem examination. Moreover, a key characteristic of the PPA‐LV case is a deterioration of phonological short‐term memory, but again little work has scrutinized the nature of this impairment over time. The current study seeks to redress these oversights and presents detailed longitudinal examination of language and memory function in a case of PPA‐LV, with special focus on tests linked to components of phonological short‐term memory function. Our findings are then considered with reference to a contemporary model of the neuropsychology of phonological short‐term memory. Additionally, post‐mortem examinations indicated Alzheimer's disease type pathology, providing further evidence that the PPA‐LV presentation may reflect an atypical presentation of this condition.